Occurrence of Parthenogenesis in Potato Tuber Moth. Issue 1 (8th February 2018) - Liu, Yan; Hu, Chun-Hua; Wang, Chun-Ya; Xiong, Yan; Li, Zong-Kai; Xiao, Chun
Abstract: Parthenogenesis, a natural form of asexual reproduction produced from unfertilized eggs, occurs in many insects in Hemiptera and Hymenoptera, but very rarely in Lepidoptera. The current study aimed to test the larval density dependent occurrence of parthenogenesis in potato tuber moth, Phthorimaea operculella (Zeller; Lepidoptera: Gelechiidae) under laboratory conditions. More than 10% of females out of 25 tested females that developed from the high larval density treatment at 45 larvae per tuber were capable to reproduce asexually. Both male and female offspring were produced parthenogenetically. The sexually reproductive offspring of a laboratory parthenogenetic population had a lower egg hatch rate, shorter larval stage, and shorter male life span when compared with the non-parthenogenetic population. This suggests that the sexually reproductive offspring of parthenogenetic population have a decreased overall fitness compared to the sexually reproductive offspring of non-parthenogenetic population.